Pesticide exposure and poisoning in Brazil: Outcome severity, clinical manifestations and management of cases reported to a poison control center. Issue 3 (16th March 2023) - dos Santos, Josefa Cristina Pereira; Valli, Joanina Bicalho; Sesse, Nixon Souza; Mackenzie Ross, Sarah; Zandonade, Eliana; Ayres, Lorena Rocha; Sampaio, Karla Nívea
Abstract: This work aimed to identify variables associated with increased risk of outcome severity as well as to describe clinical manifestations/symptoms and management of pesticide-related cases reported to a poison center in Brazil. An increased risk of more severe outcomes was observed when exposures occurred in rural areas, involved suicide attempts and moderately to extremely hazardous pesticides. Clinical manifestations with higher frequencies included vomiting, nausea, sialorrhea, headache, miosis and sweating. From the treatment initially applied to the patient, 51.91% encompassed gastric lavage, but this procedure was only recommended in 20.01% of cases by the CIATox. Identifying risk factors associated with poor outcome, describing clinical manifestations, and contrasting initial treatment measures adopted against those recommended by the Poison Center can help determine diagnosis, prognosis and ensure appropriate clinical interventions are used in cases of pesticide poisoning.